2014
DOI: 10.1007/978-1-4939-1221-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Piwi Proteins and piRNAs Step onto the Systems Biology Stage

Abstract: Animal germ cells are totipotent because they maintain a highly unique and specialized epigenetic state for its genome. To accomplish this, germ cells express a rich repertoire of specialized RNA binding protein complexes such as the Piwi proteins and Piwi-interacting RNAs (piRNAs): a germ-cell enriched pathway of the RNA interference (RNAi) phenomenon which includes microRNA and endogenous small interfering RNA pathways. Piwi proteins and piRNAs are deeply conserved in animal evolution and play essential role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 206 publications
(319 reference statements)
0
14
0
Order By: Relevance
“…49 and used to validate and confirm DEGs. Our study validated DEGs between testis and ovary using qRT-PCR for 21 genes that had previously been demonstrated as involved in gonadal development in teleosts and were specifically expressed in germ cells in various animals [50][51][52][53][54][55][56][57][58] . Our findings showed a significantly positive correlation of DEG analysis results between RNA-seq and qRT-PCR, particularly for DEGs that had a high log 2 fold change.…”
Section: Discussionmentioning
confidence: 55%
“…49 and used to validate and confirm DEGs. Our study validated DEGs between testis and ovary using qRT-PCR for 21 genes that had previously been demonstrated as involved in gonadal development in teleosts and were specifically expressed in germ cells in various animals [50][51][52][53][54][55][56][57][58] . Our findings showed a significantly positive correlation of DEG analysis results between RNA-seq and qRT-PCR, particularly for DEGs that had a high log 2 fold change.…”
Section: Discussionmentioning
confidence: 55%
“…Increasing evidence highlights the importance of AGO activity in plant germline development and gamete formation (Nonomura et al, 2007;Wüest et al, 2010;Olmedo-Monfil et al, 2010;Singh et al, 2011;Borges et al, 2011;Tucker et al, 2012). This is reminiscent of the role of AGO proteins in the animal germline; proteins of the animal-specific PIWI-clade protect the genomic integrity of the germline, in particular by repressing the activity of transposons in invertebrates, although their role in vertebrates is less clear (Clark and Lau, 2014). AGO/PIWI proteins, and potentially other proteins involved in small RNA pathways, interact with VASA or VASA-like RNA helicases that are preferentially expressed in the germline (Yajima and Wessel, 2011).…”
Section: The Acquisition and Restriction Of Reproductive Fatementioning
confidence: 99%
“…61 Recent studies have demonstrated that piRNAs and PIWI proteins play vital roles in developments of germ cells and fertility, 62 as mutations that knockout either PIWI protein function or piRNA biogenesis, resulting in germ cell death, gonadal atrophy, and finally sterility in invertebrates and vertebrates. 63 PIWIL1/HIWI, PIWIL2/HILI, PIWIL3/HIWI3, and PIWIL4/HIWI2 are four human PIWIs, 57 while the mouse genome only encodes three PIWI homologs including Piwil1/Miwi, Piwil2/Mili, and Piwil4/Miwi2. 64 The role of piRNAs during spermatogenesis is confirmed by the known functions of their partner, the PIWI proteins.…”
Section: Mirna Spermatogenesis and Male Fertilitymentioning
confidence: 99%